Emergence of resilience : a behavior model to understand stress-coping - Gustaman, Gorby Nicholas (2015)
Stressful experiences in early life increase an individual’s vulnerability to stress-related disorders while positive enrichment improves resiliency to stress. This study investigated the underlying morphological changes in the CA3 region of the hippocampus that brought about this variation on Wistar rats. Effects of stress and enrichment were observed independently and in interaction with each other. Early life stress was provided through neonatal maternal separation (MS) while environmental enrichment (EE) was provided through group-housing in large cage filled with novel stimuli in adulthood. Control group was raised in absence of MS and in standard laboratory cage. Following brain collection, CA3 neuron tracing was carried out on Golgi-stained sections using a microscope. The images drawn were analyzed using Sholl analysis to obtain the total number of branch points (BP) and total dendritic length (DL) which were then compared and statistically analyzed. Resulting data shows that MS significantly decreases both total number of BP and DL while EE did not significantly rescue these morphological deficits induced by MS. Therefore, the data suggest that MS increases an individual’s stress vulnerability through structural damage in the CA3 region and the current EE model was insufficient to compensate for the potency of MS damage.